Feasibility of six-month outpatient cognitive remediation in schizophrenia: Experience from the randomized controlled integrated social cognition and social skills therapy study - Tim Schuster; Agnes Lowe; Karolin Weide; Daniel Kamp; Mathias Riesbeck; Andreas Bechdolf; Anke Brockhaus-Dumke; René Hurlemann; Ana Muthesius; Stefan Klingberg; Martin Hellmich; Sabine Schmied; et al. (Schizophrenia Research: Cognition, 2023)
Patients with schizophrenia often have cognitive impairments that contribute to diminished psychosocial functioning. Cognitive remediation therapy (CRT) has proven efficacy and is recommended by evidence-based treatment guidelines. Important moderators of efficacy include integration of CRT into a psychiatric rehabilitation concept and patient attendance at a sufficient number of therapy sessions. These conditions can probably best be met in an outpatient setting; however, outpatient treatment is prone to higher rates of treatment discontinuation and outpatient settings are not as well protected as inpatient ones and less closely supervised.The present study investigated the feasibility of outpatient CRT in schizophrenia over a six-month period. Adherence to scheduled sessions and safety parameters were assessed in 177 patients with schizophrenia randomly assigned to one of two matched CRT programs.Results showed that 58.8 % of participants completed the CRT (>80 % of scheduled sessions) and 72.9 % completed at least half the sessions. Predictor analysis revealed a high verbal intelligence quotient as favorable for good adherence, but this factor had only low general predictive power. During the six-month treatment phase, serious adverse events occurred in 15.8 % (28/177) of the patients, which is a comparable rate to that reported in the literature.Our findings support the feasibility of six-month outpatient CRT in schizophrenia in terms of adherence to scheduled sessions and safety. Trial registration number: NCT02678858, DRKS00010033.